Whither Latin American Capital Markets? - De La Torre, Augusto; Schmukler, Sergio L. (World Bank, Washington, DC, 2017)
In this study, the authors analyze where we stand and where we are heading on capital market development. More specifically, this study has three main goals. First, the authors take stock of the state and evolution of Latin American capital markets and related reforms, over time and relative to other countries. Second, authors analyze the factors driving the development of capital markets, with particular interest on measuring the impact of reforms. Third, in light of this analysis, authors discuss the prospects for capital market development in Latin America and emerging economies in general, and the implications for the reform agenda going forward. To understand the state and future of capital markets in developing countries, the report consists of three additional chapters. Chapter two documents the main developments in international financial markets and the increasing globalization process. The chapter also describes the influence of these worldwide trends on Latin America, with particular attention to the effects on the policies and reforms adopted. Chapter three evaluates the factors behind the development (or lack of development) of capital markets. The chapter first studies how different macroeconomic and institutional variables affect the development of domestic stock and bond markets and their internationalization. The second part of chapter three analyzes the effects of reforms on capital markets. The chapter finishes by examining whether the experience of Latin America is similar to that of other regions. Finally, chapter four discusses the future of capital markets in developing countries, the policy implications, and the lessons for the reform agenda.